1986
DOI: 10.1139/m86-114
|View full text |Cite
|
Sign up to set email alerts
|

R-plasmid transfer in soil and water

Abstract: R-plasmid transfer in Escherichia coli was investigated in nutrient broth, sterile soil, and sterile stream water. Plasmid transfer occurred in broth cultures at 30 and 22 degrees C, but not at 15 degrees C. R-plasmid transfer was not observed at 30, 22, and 15 degrees C in nonamended sterile soil and stream water. The addition of nutrients to sterile stream water and soil allowed plasmid transfer to occur at temperatures ranging from 15 to 30 degrees C. R-plasmid transfer was also observed in soil adjusted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…According to the results of the present study, incubation temperatures of 4 and 15°C did not favor the transfer of integron-mediated antibiotic resistance genes in bovine feces and storm water. Previous studies showed that a temperature higher than 15°C was required for conjugal transfer of R-plasmids between E. coli cells (21,23). Singleton and Anson (21) found that transfer of an R-plasmid between E. coli cells occurred at 17 to 37°C when they studied the transfer of the plasmid at six different temperatures, 15, 17, 20, 22, 27, and 37°C; no transconjugants were obtained when the conjugation experiment was conducted at 15°C.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present study, incubation temperatures of 4 and 15°C did not favor the transfer of integron-mediated antibiotic resistance genes in bovine feces and storm water. Previous studies showed that a temperature higher than 15°C was required for conjugal transfer of R-plasmids between E. coli cells (21,23). Singleton and Anson (21) found that transfer of an R-plasmid between E. coli cells occurred at 17 to 37°C when they studied the transfer of the plasmid at six different temperatures, 15, 17, 20, 22, 27, and 37°C; no transconjugants were obtained when the conjugation experiment was conducted at 15°C.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of environmental parameters (including temperature, pH, nutrient concentration, salinity and metal ions) on plasmid transfer have been previously investigated by a number of other groups (Singleton & Anson, 1981 ;Gauthier e t al., 1985;Trevors & Oddie, 1986;Khalil & Gealt, 1987;Van Elsas e t al., 1987;Rochelle e t al., 1989;Fernandez-Astorga e t al., 1992). The approach of all these studies differed from that of the present paper in that they measured the frequency of plasmid transfer in response to variation of environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic factors such as competition, antagonism and prédation might also affect transfer frequencies. It should be stressed that, so far, most data on plasmid transfer in soil have been obtained using a system of introduced donor and recipient bacteria and mobilizable or broad-host-range self-transmissible plasmids [17,[34][35][36][37]. These data represent a "worst case scenario", rather unrealistic for the planned releases in which heterologous DNA will mainly be present on the chromosome.…”
Section: Genetic Stability and Gene Tvansfermentioning
confidence: 99%